2014
DOI: 10.13065/jksdh.2014.14.01.123
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between life satisfaction and oral health practice in high school students

Abstract: Objectives : The purpose of the study is to investigate the relationship between the life satisfaction of high school students and their oral health practice and to provide the right method of oral health maintenance.Methods : The subjects were 307 high school students in Chungcheongnam-do. A self-reported questionnaire was filled out from May 13 to 28, 2013. The questionnaire included life satisfaction and oral health practice. Data were analyzed by SPSS 12.0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
1
0
1
Order By: Relevance
“…Song (2006), Shin et al(2011) reported that the higher in smartphone addiction score, somatization, depression, anxiety, hostility, psychosis were higher [19,20]. These findings suggest that problems with smartphone e-mail may have a considerable effect on the emotional status of young teens.…”
Section: Differences Of Mental Health By Groupsmentioning
confidence: 99%
“…Song (2006), Shin et al(2011) reported that the higher in smartphone addiction score, somatization, depression, anxiety, hostility, psychosis were higher [19,20]. These findings suggest that problems with smartphone e-mail may have a considerable effect on the emotional status of young teens.…”
Section: Differences Of Mental Health By Groupsmentioning
confidence: 99%
“…그로인해 구강건강 및 건강을 유지하는데 문제가 발생하고 개개인의 삶의 질에 영 향을 미치게 된다 15) . 최근에는 구강건강측정에 있어서도 구 강질환이 일상생활과 삶의 질에 미치는 영향을 측정하는 것 에 관심을 기울이며 삶의 질을 추구함에 있어 다른 어떤 문 제보다도 구강건강이 중요하다는 인식이 높아짐에 따라 삶 의 질에 관한 연구가 초등학생 16) , 중학생 13,17) , 고등학생 11,18,19) , 일반성인 1,2) , 노인 20,21) , 근로자 The same letters means that the intergroup differences were not statistically significant(p>0.05) p-value was calculated by t-test or one-way ANOVA. The same letters means that the intergroup differences were not statistically significant(p>0.05) p-value was calculated by t-test or one-way ANOVA.…”
unclassified